A Novel Design of Thermos Cup with Thermostat Control based on TRIZ Theory - Liangliang Yang, Yi Feng (Forest Chemicals Review, 1970)
Based on TRIZ theory, this work presents a novel methodology for designing thermos cup with thermostat control. In the design processes, this work first presented the system function, system causality chain, and system nine-screen method, then used technical contradiction, physical contradiction and object-field analysis method to obtain the solution to the problems. Finally, the optimal scheme was evaluated and selected by combing various schemes of early analysis and problem solving. The TRIZ theory offers a new idea for the design of thermos cup with thermostat control, and its solution processes also verified the feasibility of the novel design.